UNUSED PRINTED-MASS MEDIA FOR TEACHING ENGLISH IN DIFFERENT TYPES OF SKILLS - Dini Puspita Wati (Fakultas Ilmu Budaya, Universitas Brawijaya, 2018)
Abstract: As language teachers, being creative has become a need to help students to achieve their best performance. This paper is intended to describe how to use the unused printed mass media, such as magazines and newspaper for teaching English to become more fun and enjoyable. Thus, the paper focuses on how the teacher can make use of the unsued printed mass—media and develop teaching materials from them. The paper also discusses the learning stages in using the unused magazine or newspaper. News paper and magazines are considered as authentic as they can be easily found in everyday life. Using the unused printed mass-media in the language classroom has many advantages because they are cheap, easy to get, fun, and environmentally friendly.Key words: Learning stages, unused-printed mass media, taching English.